The Molopo Farms Complex, Botswana: History, Stratigraphy, Petrography, Petrochemistry and Ni-Cu-PGE Mineralization (7cbfd5e2-2a0e-4041-96d5-f3f5caa4ab01) - EJ. Reichhardf (Canadian Institute of Mining, Metallurgy and Petroleum, 1994)
The Molopo Farms Complex is a major, layered ultramafic/mafic, early Proterowic intrusion which is totally covered by sediments of the Karoo and Kalahari Fonnations and situated in southern Botswana and northeastern South Africa. The approximately 3000 m thick, generally fine- to medium-grained ultramafic and mafic cumulates are intrusive into equivalents of Thmsvaal Supergroup sediments and lavas. Multiphase defonnation resulted in tilting and segmentation of the Complex into individual tectonic blocks. Sr isotopes document at least two chemically distinct parental liquids which interacted in a complex manner to form an approximately 1000 m thick rhythmically layered succession which straddles the ultramafic/mafic boundary. Repeated mixing resulted in a complex cryptic layering pattern and numerous sulfide-enriched layers which contain significant PGE+Au concentrations.